Valence isomerization of cyclohepta-1,3,5-triene and its heteroelement analogues - Jansen, Helen; Slootweg, J. Chris; Lammertsma, Koop (Beilstein Journal of Organic Chemistry, 2011)
The valence isomerization of the all-carbon and heteroelement analogues of cyclohepta-1,3,5-triene into the corresponding bicyclo[4.1.0]hepta-2,4-dienes is reviewed to show the impact of the heteroatom on the stability of both valence isomers. The focus is on the parent systems and their synthetic applications.
Keywords: aromaticity; cycloheptatriene; heteroatom; valence isomerization

(untitled) - Vogel, E. (Angew. Chem., Int. Ed., 2011)

(untitled) - Maier, G. (Angew. Chem., Int. Ed. Engl., 1967)

(untitled) - Rodríguez-Hahn, L.; Esquivel, B.; Sánchez, A. A.; Cárdenas, J.; Tovar, O. G.; Soriano-García, M.; Toscano, A. (J. Org. Chem., 1988)

(untitled) - Güney, M.; Daştan, A.; Balci, M. (Helv. Chim. Acta, 2005)

(untitled) - Borst, M. L. G.; Bulo, R. E.; Winkel, C. W.; Gibney, D. J.; Ehlers, A. W.; Schakel, M.; Lutz, M.; Spek, A. L.; Lammertsma, K. (J. Am. Chem. Soc., 2005)

(untitled) - Borst, M. L. G.; Bulo, R. E.; Gibney, D. J.; Alem, Y.; de Kanter, F. J. J.; Ehlers, A. W.; Schakel, M.; Lutz, M.; Spek, A. L.; Lammertsma, K. (J. Am. Chem. Soc., 2005)

(untitled) - Jansen, H.; Slootweg, J. C.; Ehlers, A. W.; Lammertsma, K. (Organometallics, 2010)

(untitled) - Couzijn, E. P. A.; Ehlers, A. W.; Slootweg, J. C.; Schakel, M.; Krill, S.; Lutz, M.; Spek, A. L.; Lammertsma, K. (Chem.–Eur. J., 2008)

(untitled) - Jansen, H.; Rosenthal, A. J.; Slootweg, J. C.; Ehlers, A. W.; Lutz, M.; Spek, A. L.; Lammertsma, K. (Organometallics, 2008)

(untitled) - Ladenburg, A. (Liebigs Ann. Chem., 1883)

(untitled) - Traetteberg, M. (J. Am. Chem. Soc., 1964)

(untitled) - Butcher, S. S. (J. Chem. Phys., 1965)

(untitled) - Reed, T. B.; Libscomb, W. N. (Acta Crystallogr., 1953)
Suitable crystals for an accurate X-ray determination could not be obtained for cyclohepta-1,3,5-triene.

(untitled) - Davis, R. E.; Tulinksy, A. (Tetrahedron Lett., 1962)
However the derivative 7,7-dimethylcycloheptatriene-3-carboxylic acid did result in suitable crystals.

(untitled) - Chen, Z.; Jiao, H.; Wu, J. I.; Herges, R.; Zhang, S. B.; von Ragué Schleyer, P. (J. Phys. Chem. A, 2008)

(untitled) - Jarzeçki, A. A.; Gajewski, J.; Davidson, E. R. (J. Am. Chem. Soc., 1999)
See for similar computational geometrical studies α = 52.1°, β= 25.2° determined at the CASSCF(6,6)/6-31G(d) level.

(untitled) - Scott, A. P.; Agranat, I.; Biedermann, P. U.; Riggs, N. V.; Radom, L. (J. Org. Chem., 1997)
α = 57.5°, β= 27.6° determined at the B-LYP/6-31G(d) level.

(untitled) - Jensen, F. R.; Smith, L. A. (J. Am. Chem. Soc., 1964)

(untitled) - Anet, F. A. L. (J. Am. Chem. Soc., 1964)

(untitled) - Nishinaga, T.; Izukawa, Y.; Komatsu, K. (J. Phys. Org. Chem., 1998)
See for determination of “Nuclear Independent Chemical Shift” (NICS(0), benzene-8.0 ppm) gives-4.2 ppm for 1.

(untitled) - Herges, R.; Geuenich, D. (J. Phys. Chem. A, 2001)

(untitled) - Maier, G. (Angew. Chem., Int. Ed. Engl., 1967)

Mechanism and Theory in Organic Chemistry - Lowry, T. H.; Richardson, K. S. (Harper and Row, 1990)

(untitled) - Menzek, A.; Balci, M. (Tetrahedron, 1993)
And references therein.

(untitled) - Rubin, M. B. (J. Am. Chem. Soc., 1981)

(untitled) - Hall, G. E.; Roberts, J. D. (J. Am. Chem. Soc., 1971)

(untitled) - Tang, T.-H.; Lew, C. S. Q.; Cui, Y.-P.; Capon, B.; Csizmadia, I. G. (J. Mol. Struct.: THEOCHEM, 1994)

(untitled) - Woods, W. G. (J. Org. Chem., 1958)

(untitled) - Klump, K. N.; Chesick, J. P. (J. Am. Chem. Soc., 1963)

(untitled) - Berson, J. A.; Willcott, M. R., III (J. Am. Chem. Soc., 1965)

(untitled) - Berson, J. A.; Willcott, M. R., III (J. Am. Chem. Soc., 1965)

(untitled) - Klärner, F.-G. (Angew. Chem., Int. Ed. Engl., 1974)

(untitled) - Klärner, K.-G.; Yaşlak, S.; Wette, M. (Chem. Ber., 1977)

(untitled) - Klärner, K.-G.; Yaşlak, S.; Wette, M. (Chem. Ber., 1979)

(untitled) - Klärner, K.-G.; Brassel, B. (J. Am. Chem. Soc., 1980)

(untitled) - Ter Borg, A. P.; Kloosterziel, H.; Van Meurs, N. (Proc. Chem. Soc., London, 1962)

(untitled) - Weth, E.; Dreiding, A. S. (Proc. Chem. Soc., London, 1964)

(untitled) - Berson, J. A.; Willcott, M. R., III (J. Am. Chem. Soc., 1966)
See for the methyl-substituted analogues.

(untitled) - Vogel, E.; Böll, W. A.; Günther, H. (Tetrahedron Lett., 1965)

(untitled) - Günther, H. (Tetrahedron Lett., 1965)

(untitled) - Pye, C. C.; Xidos, J. D.; Poirier, R. A.; Burnell, D. J. (J. Phys. Chem. A, 1997)

(untitled) - Kassaee, M. Z.; Arshadi, S.; Haerizade, B. N.; Vessally, E. (J. Mol. Struct.: THEOCHEM, 2005)

(untitled) - Cremer, D.; Dick, B.; Christeu, D. (J. Mol. Struct.: THEOCHEM, 1984)

(untitled) - Kao, J. (J. Comput. Chem., 1988)

(untitled) - Jennings, W. B.; Rutherford, M.; Boyd, D. R.; Agarwal, S. K.; Sharma, N. D. (Tetrahedron, 1988)

(untitled) - Jennings, W. B.; Rutherford, M.; Agarwal, S. K.; Boyd, D. R.; Malone, J. F.; Kennedy, D. A. (J. Chem. Soc., Chem. Commun., 1986)

(untitled) - Kassaee, M. Z.; Cheshmehkani, A.; Musavi, S. M.; Majdi, M.; Motamedi, E. (J. Mol. Struct.: THEOCHEM, 2008)

(untitled) - Chen, Z.; Wannere, C. S.; Corminboeuf, C.; Puchta, R.; von Ragué Schleyer, P. (Chem. Rev., 2005)
The NICS value is obtained from NMR calculations of a ghost atom (Bq) at the geometrical ring center (NICS(0)), but the value 1 Å above the ring (NICS(1)) is recommended, because a lack of σ shielding makes it a better measure of π-electron delocalization.

(untitled) - Kassaee, M. Z.; Musavi, S. M.; Momeni, M. R.; Shakib, F. A.; Ghambarian, M. (J. Mol. Struct.: THEOCHEM, 2008)
See for IAO-B3LYP/6-311G(d)//B3LYP/6-311G(d) level of theory.

(untitled) - Karney, W. L.; Kastrup, C. J.; Oldfield, S. P.; Rzepa, H. S. (J. Chem. Soc., Perkin Trans. 2, 2002)

(untitled) - Dewar, M. J. S.; Trinajstić, N. (J. Am. Chem. Soc., 1970)

(untitled) - Hess, B. A., Jr; Schaad, L. J. (J. Am. Chem. Soc., 1973)

(untitled) - Vogel, E.; Schubart, R.; Böll, W. A. (Angew. Chem., Int. Ed. Engl., 1964)

(untitled) - van Tamelen, E. E.; Carty, D. T. (J. Am. Chem. Soc., 1967)

(untitled) - Vogel, E.; Günther, H. (Angew. Chem., Int. Ed. Engl., 1967)

Seven-membered and Larger Rings and Fused Derivatives - Belen’kll, L. I. (Oxepanes and Oxepines, 1996)

(untitled) - Bock, C. W.; George, P.; Stezowski, J. J.; Glusker, J. P. (Struct. Chem., 1989)

(untitled) - Hayes, D. M.; Nelson, S. D.; Garland, W. A.; Kollman, P. A. (J. Am. Chem. Soc., 1980)

(untitled) - Vogel, E.; Klärner, F.-G. (Angew. Chem., Int. Ed. Engl., 1968)

(untitled) - Klärner, F.-G.; Vogel, E. (Angew. Chem., Int. Ed. Engl., 1973)

Biogenic Amines and Physiological Membranes in Drug Therapy, Part B - Jerina, D. M.; Daly, J. W.; Witkop, B. (Marcel Dekker, 1971)

(untitled) - Daly, J. W.; Jerina, D. M.; Witkop, B. (Experientia, 1972)

(untitled) - Jerina, D. M.; Daly, J. W. (Science, 1974)

(untitled) - Boyd, D. R.; Sharma, N. D. (Chem. Soc. Rev., 1996)

(untitled) - Klotz, B.; Barnes, I.; Becker, K. H.; Golding, B. T. (J. Chem. Soc., Faraday Trans., 1997)

(untitled) - Henderson, A. P.; Mutlu, E.; Leclercq, A.; Bleasdale, C.; Clegg, W.; Henderson, R. A.; Golding, B. T. (Chem. Commun., 2002)

(untitled) - George, P.; Bock, C. W.; Glusker, J. P. (J. Phys. Chem., 1990)
In the presence of acid, protonation results in a carbocation intermediate and does not generate a radical species.

(untitled) - Holovka, J. M.; Gardner, P. D. (J. Am. Chem. Soc., 1967)

(untitled) - Gillard, J. R.; Newlands, M. J.; Bridson, J. N.; Burnell, D. J. (Can. J. Chem., 1991)

Seven-Membered Heterocyclic Compounds Containing Oxygen and Sulfur - Field, L.; Tuleen, D. L. (Monocyclic Seven-Membered Rings Containing Sulfur, 1972)

(untitled) - Miller, K. J.; Moschner, K. F.; Potts, K. T. (J. Am. Chem. Soc., 1983)

(untitled) - Gleiter, R.; Krennrich, G.; Cremer, D.; Yamamoto, K.; Murata, I. (J. Am. Chem. Soc., 1985)

(untitled) - Nishino, K.; Takagi, M.; Kawata, T.; Murata, I.; Inanaga, J.; Nakasuji, K. (J. Am. Chem. Soc., 1991)

(untitled) - Reinhoudt, D. N.; Kouwenhoven, C. G. (Tetrahedron, 1974)

(untitled) - Yamamoto, K.; Yamazaki, S.; Kohashi, Y.; Murata, I.; Kai, Y.; Kanehisa, N.; Miki, K.; Kasai, N. (Tetrahedron Lett., 1982)

Seven-membered and Larger Rings and Fused Derivatives - Yamamoto, K.; Yamazaki, S. (Thiepanes and Thiepines, 1996)

(untitled) - Ueda, I.; Sato, Y.; Maeno, S.; Umio, S. (Chem. Pharm. Bull., 1978)

(untitled) - Higashi, Y.; Momotani, Y.; Suzuki, E.; Kaku, T. (Pharmacopsychiatry, 1987)

Science of Synthesis - Schwan, A. L. (Product Subclass 4: Benzothiepins and Selenium/Tellurium Analogues, 2004)

(untitled) - Protiva, M. (J. Heterocycl. Chem., 1996)

(untitled) - Paquette, L. A. (Angew. Chem., Int. Ed. Engl., 1971)

(untitled) - Hafner, K. (Angew. Chem., Int. Ed. Engl., 1964)

(untitled) - Vogel, E.; Altenbach, H.-J.; Drossard, J.-M.; Schmickler, H.; Stegelmeier, H. (Angew. Chem., Int. Ed. Engl., 1980)

Part 5: Small and Large Rings - Smalley, R. K. (Azepines, 1984)

Part 5: Small and Large Rings - Smalley, R. K. (Azepines, 1984)

(untitled) - Lindner, H. J.; von Gross, B. (Chem. Ber., 1972)

(untitled) - Smith, D. A.; Bitar, J. (J. Org. Chem., 1993)

(untitled) - Prinzbach, H.; Babsch, H.; Fritz, H.; Hug, P. (Tetrahedron Lett., 1977)

(untitled) - Paquette, L. A.; Kuhla, D. E.; Barrett, J. H.; Leichter, L. M. (J. Org. Chem., 1969)

(untitled) - van den Hende, J. H.; Kende, A. S. (Chem. Commun., 1965)

(untitled) - Paquette, L. A.; Barrett, J. H. (J. Am. Chem. Soc., 1966)

(untitled) - Paquette, L. A.; Barrett, J. H.; Kuhla, D. E. (J. Am. Chem. Soc., 1969)

(untitled) - Paquette, L. A.; Barrett, J. H. (J. Am. Chem. Soc., 1966)

(untitled) - Paquette, L. A.; Kuhla, D. E.; Barrett, J. H. (J. Org. Chem., 1969)

Seven-membered and Larger Rings and Fused Derivatives - Le Count, D. J. (Azepines and their Fused-ring Derivatives, 1996)
See for more details on azepines.

Science of Synthesis - Meigh, J.-P. K. (Product Subclass 6: Benzazepines and Their Group 15 Analogues, 2004)
See for more synthetic routes.

(untitled) - Robey, R. L.; Copley-Merriman, C. R.; Phelps, M. A. (J. Heterocycl. Chem., 1989)

(untitled) - Steiner, G.; Franke, A.; Hädicke, E.; Lenke, D.; Teschendorf, H.-J.; Hofmann, H.-P.; Kreiskott, H.; Worstmann, W. (J. Med. Chem., 1986)

(untitled) - Muedas, C. A.; Schröder, D.; Sülzle, D.; Schwarz, H. (J. Am. Chem. Soc., 1992)

(untitled) - Märkl, G.; Schubert, H. (Tetrahedron Lett., 1970)

(untitled) - Märkl, G.; Burger, W. (Angew. Chem., Int. Ed. Engl., 1984)

(untitled) - Märkl, G.; Burger, W. (Tetrahedron Lett., 1983)

(untitled) - Kurita, J.; Shiratori, S.; Yasuike, S.; Tsuchiya, T. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Yasuike, S.; Ohta, H.; Shiratori, S.; Kurita, J.; Tsuchiya, T. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Segall, Y.; Shirin, E.; Granoth, I. (Phosphorus Sulfur Relat. Elem., 1980)

(untitled) - Yasuike, S.; Kiharada, T.; Kurita, J.; Tsuchiya, T. (Chem. Commun., 1996)

(untitled) - Yasuike, S.; Kiharada, T.; Tsuchiya, T.; Kurita, J. (Chem. Pharm. Bull., 2003)

Seven-membered and Larger Rings and Fused Derivatives - Pabel, M.; Wild, S. B. (Rings containing Phosphorus, 1996)
See for more details on phosphepines.

(untitled) - Jansen, H.; Samuels, M. C.; Couzijn, E. P. A.; Slootweg, J. C.; Ehlers, A. W.; Chen, P.; Lammertsma, K. (Chem.–Eur. J., 2010)

Science of Synthesis - Slootweg, J. C.; Lammertsma, K. (Product Class 2: Phosphinidenes and termian Phosphinidene Complexes, 2009)

(untitled) - Lammertsma, K. (Top. Curr. Chem., 2003)

(untitled) - Mathey, F. (Angew. Chem., Int. Ed., 2003)

(untitled) - Le Floch, P. (Coord. Chem. Rev., 2006)

(untitled) - Noonan, K. J. T.; Gates, D. P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Gates, D. P. (Top. Curr. Chem., 2005)